Pemanfaatan Tanaman Pandanus tectorius pada Aspek Ekonomi Kreatif : Studi Etnobotani pada UMKM di Pandeglang, Banten - Lina Nurahma Sari; Nasha Nurfadilah; Bilqis Zalva Denero; Aulia Azizah Rahmah; Rr. Efya Salma Sulistya; Desi Eka Nur Fitriana (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Pandanus tectorius is a non-timber forest product that has important ecological, cultural, and economic value for coastal communities. This study aims to analyze the utilization of Pandanus tectorius in MSME-based creative industries through an ethnobotanical approach in Banjar District, Pandeglang Regency, Banten. This approach is used to examine local knowledge, processing techniques, and pandan cultural values in the community's economic system. Data was collected through in-depth interviews, observation of the production process, and descriptive analysis. The results show that pandans have been used for generations as the main raw material for various woven products, such as mats, hats, and bags. Based on field findings, pandan handicraft activities involve more than 100 active and growing weavers in the last five years, with a marketing reach to the national level as well as limited-scale exports. However, the development of pandan crafts still faces obstacles in the form of limited raw materials due to land conversion, the lack of regeneration of young artisans, and limited production technology. These findings affirm the importance of integrating ethnobotanical knowledge in strengthening MSMEs and developing a sustainable pandan creative industry.